(untitled) (Mustansiria Dental Journal, 2018)
Candida is a genus of yeast .Many species of this genus are symbiont of animals host including humans. While usually living as commensally in oral cavity, some candida can cause disease .The most significant member of the genus is candida albicans which can cause infection called candidiasis or thrush especially in elderly denture wearers.So the denture seems to be frequently the sources of fungal infection. The current study aimed to determine the fungal prevalence rate in oral cavity among denture wearers patients in comparison to those without dentures and also to determine the local risk factors includes trauma due to ill fitting denture, nocturnal wear of the denture, heavy smoking and the age of the denture. The result of this study showed that the prime etiology of candida growth was the material of prosthesis itself. 57% of the denture wearers showed growth of candida while 22% of subjects who had their own dentitions showed candida growth that the prosthesis is the dominant etiological factors in candida growth other local factors must be considered.